Consequences of grain boundary barriers on electrical characteristics of CIGS solar cells - Urbaniak, A.; Czudek, A.; Eslam, A.; Wuerz, R.; Igalson, M. (Solar energy materials and solar cells, 2023)
The following work deals with interpreting defect spectroscopy results for CIGS solar cells. The motivation and brief background for defect physics investigation in photovoltaic materials is presented. Since the subject of defect spectroscopy interpretation in CIGS has been discussed for many years and plenty of experimental results are available, we present here those that we believe are the most important. Characteristic and essential features of signals observed in CIGS are shown, which have eluded unambiguous interpretation and made it impossible to propose a coherent physical mechanism so far. The physical models co-existing in the CIGS community are also briefly discussed. Emphasis is placed on which features of the observed signals are explained by models and which are not. The main aim of the presented work is to introduce a new model describing the results of admittance spectroscopy in CIGS solar cells based on the existence of hole barriers at the grain boundaries. Most completely, the presented model explains the characteristic features of the measured signals, including the variability of the activation energy of the observed processes, its dependence on the hole concentration, and its correlation with the results of conductivity measurements. The model assumptions and simulation results show how the concentration of surface donors at the grain boundaries affects the height of the grain boundary barriers and the measured concentration of holes in the CIGS. The simulations are presented for different grain sizes and confronted with experimental results. •New model explaining admittance and DLTS results in CIGS solar cells.•Hole barriers at the grain boundaries make grains partially depleted, lowering the measured hole concentration.•Thermally activated hole capture accounts for the variable activation energy.•The hole barrier height is visible as the activation energy both in the admittance and conductivity measurements.•Provides a physical mechanism for correlation of admittance and DLTS signal with the hole concentration.